A Video Browsing Tool for Content Management in Postproduction - Werner Bailer; Wolfgang Weiss; Gert Kienast; Georg Thallinger; Werner Haas (International Journal of Digital Multimedia Broadcasting)
We propose an interactive video browsing tool for supporting content management and selection in postproduction. The approach is based on a process model for multimedia content abstraction. A software framework based on this process model and desktop and Web-based client applications are presented. For evaluation, we apply two TRECVID style fact finding approaches (retrieval and question answering tasks) and a user survey to the evaluation of the video browsing tool. We analyze the correlation between the results of the different methods, whether different aspects can be evaluated independently with the survey, and if a learning effect can be measured with the different methods, and we also compare the full-featured desktop and the limited Web-based user interface. The results show that the retrieval task correlates better with the user experience according to the survey. The survey rather measures the general user experience while different aspects of the usability cannot be analyzed independently.